2012
DOI: 10.3109/17482941.2011.655293
|View full text |Cite
|
Sign up to set email alerts
|

Lactate clearance in cardiogenic shock following ST elevation myocardial infarction: A pilot study

Abstract: In patients with CS following STEMI, 12-h lactate clearance<10% identifies a subset of patients at higher risk for death at short and long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 29 publications
2
30
0
2
Order By: Relevance
“…It is a marker of poor outcome if measured during the initial 24 h of intensive care unit admission in CS [5] or in overall critically ill patient population [6]. Our study confirmed the prognostic value of lactate during the first 24 h in CS.…”
Section: Discussionsupporting
confidence: 80%
“…It is a marker of poor outcome if measured during the initial 24 h of intensive care unit admission in CS [5] or in overall critically ill patient population [6]. Our study confirmed the prognostic value of lactate during the first 24 h in CS.…”
Section: Discussionsupporting
confidence: 80%
“…One pilot study advocated that 12-h lactate clearance <10% identifies a subset of patients at higher risk for death over the short- and long-term among patients with cardiogenic shock following AMI 21. In our study, lower lactate clearance for 48 hours (<70%) remained a significant predictor of in-hospital mortality after adjusting for covariates.…”
Section: Discussionsupporting
confidence: 46%
“…Lactic acidosis typically occurs when cells are short of oxygen, forcing them to metabolize glucose anaerobically, which leads to lactate formation. Therefore, elevated lactate is indicative of tissue hypoxia as well as hypoperfusion, which occurs amongst other incidences during shock (14)(15)(16).…”
Section: Page 5 Of 18mentioning
confidence: 99%